Managing the dual business model trade-off in multinational corporations - Sergei Mozheiko; Kristian J. Sund (Journal of Business Models (JOBM), 2024)
When a multinational operates different business models in different markets, a trade-off typically exists between local-market adaptations and cross-market economies of scale and scope. How do country managers navigate these trade-offs and the tensions inherent in developing and operating such dual business models? In this short paper we explore how a local subsidiary can innovate its business model in a way that creates alignment with the local market while respecting the larger corporate structure. We study the Chinese subsidiary of Velux, a multinational window manufacturer, that has transformed its business model from simple production to engineering, and further to modular solutions. We show that by respecting both the corporate strategic mission and the corporate culture, in combination with avoiding any direct challenge to the core corporate business model, the subsidiary has bypassed the tensions commonly observed with dual business models.
Keywords: 650; business model innovation; multinational corporation; dual business models